2016
DOI: 10.5935/0004-2749.20160008
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic status of severely disabled and visually impaired elderly people in Turkey

Abstract: Purpose: To identify the prevalence of ophthalmologic diseases in elderly patients who had been classified as severely disabled and to identify the ophthalmologic conditions leading to visual impairment and blindness. Methods: The medical records of 2806 patients who had applied to the Health Board of the Erzurum Region Training and Research Hospital between January 2011 and December 2012 were reviewed. One hundred ninety-nine patients aged >64 years who were classified as severely disabled with disability rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…In many studies, neurological disorders have been found to contribute most to severe disability (3,5,15). This is consistent with the findings of our study.…”
Section: Distribution Of Diseases That Cause Severe Disabilitysupporting
confidence: 83%
See 1 more Smart Citation
“…In many studies, neurological disorders have been found to contribute most to severe disability (3,5,15). This is consistent with the findings of our study.…”
Section: Distribution Of Diseases That Cause Severe Disabilitysupporting
confidence: 83%
“…The Turkish Statistical Institute declared the prevalence of total disability in 2002 to be 12.29% (4). Few studies have been performed with the Turkish population regarding the causes of various levels of disability (5,6). Izmir is the third most populated city of Turkey, located in the south-west part of the country (7).…”
Section: Introductionmentioning
confidence: 99%
“…al. 11 also selected their study population from medical board records and studied subjects aged 64 years or over. They found that cataract, glaucoma, and AMD were the common ocular diseases causing severe disabilities in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Kıvanç et al also investigated the health board records to identify the ophthalmologic conditions leading to blindness and visual impairment in severely disabled patients aged over 64 years in Turkey (22). They found that the most common ophthalmologic diseases in that group were cataract, glaucoma, and age-related macular degeneration (AMD) with cataract being the main cause of blindness in their study.…”
Section: Figure 2 Distribution Of Causes Of Msvi Based On Age Groupsmentioning
confidence: 99%